Surface-active organic matter induces salt morphology transitions during new atmospheric particle formation and growth - Daskalakis, Vangelis; Charalambous, Fevronia; Demetriou, Constantinos; Georgiou, Georgia (My University, 2015)
.The creation of new atmospheric particles via nucleation is an important source of the particles from which Cloud Condensation Nuclei (CCN) are formed. The new particle formation (NPF) process can significantly alter the atmospheric aerosol size distribution and thus CCN activation. CCN are associated with boundary layer evolution, cloud formation, and cloud properties like albedo, or the lifetime. Water vapor condenses upon atmospheric particulates that grow in size to form cloud droplets. Despite its importance, NPF is poorly understood at the atomic level and the ns time scale especially when organic matter (OM) effects are included. Here we employ molecular dynamics simulations on ammonium chloride wet aerosol models. Salt within the aerosol is found to transition between different morphologies-brine and crystalline-depending on the presence of OM on the surface of the occurring particle. Particle number, size and growth dynamics are associated with this variant salt morphology. Our findings elucidate the dynamics of NPF and particle growth in the presence of OM.
Keywords: Aerosols; Atmospheric aerosols; Biogeochemistry; Biological materials; Boundary layers; Molecular dynamics